Beyond the Paris Agreement: Intellectual Property, Innovation Policy, and Climate Justice - Matthew Rimmer (Laws, 2019)
The multidisciplinary field of climate law and justice needs to address the topic of intellectual property, climate finance, and technology transfer to ensure effective global action on climate change. The United Nations Framework Convention on Climate Change 1992 (UNFCCC) established a foundation for the development, application and diffusion of low-carbon technologies. Against this background, it is useful to analyse how the Paris Agreement 2015 deals with the subject of intellectual property, technology transfer, and climate change. While there was discussion of a number of options for intellectual property and climate change, the final Paris Agreement 2015 contains no text on intellectual property. There is text, though, on technology transfer. The Paris Agreement 2015 relies upon technology networks and alliances in order to promote the diffusion and dissemination of green technologies. In order to achieve technology transfer, there has been an effort to rely on a number of formal technology networks, alliances, and public⁻private partnerships—including the UNFCCC Climate Technology Centre and Network (CTCN); the World Intellectual Property Organization’s WIPO GREEN; Mission Innovation; the Breakthrough Energy Coalition; and the International Solar Alliance. There have been grand hopes and ambitions in respect of these collaborative and co-operative ventures. However, there have also been significant challenges in terms of funding, support, and operation. In a case of innovation policy pluralism, there also seems to be a significant level of overlap and duplication between the diverse international initiatives. There have been concerns about whether such technology networks are effective, efficient, adaptable, and accountable. There is a need to better align intellectual property, innovation policy, and technology transfer in order to achieve access to clean energy and climate justice under the framework of the Paris Agreement 2015. At a conceptual level, philosophical discussions about climate justice should be grounded in pragmatic considerations about intellectual property and technology transfer. An intellectual property mechanism is necessary to provide for research, development, and deployment of clean technologies. There is a need to ensure that the technology mechanism of the Paris Agreement 2015 can enable the research, development, and diffusion of clean technologies at a scale to address the global challenges of climate change.